Roles of Inflammasome in Cigarette Smoke-Related Diseases and Physiopathological Disorders: Mechanisms and Therapeutic Opportunities - Ma, Yiming; Long, Yingjiao; Chen, Yan (Frontiers in Immunology, 2021)
Cigarette smoke damages a wide range of immunological functions, including innate and adaptive immune responses. Emerging literature demonstrates that inflammasome constitutes an essential component in innate immune response. In this review, we focus on the cumulative mechanisms of inflammasome in cigarette smoke-related diseases and physiopathological disorders, and summarize potential therapeutic opportunities targeting inflammasome. This review suggests that inflammasomes (NLRP3, NLRP6, NLRP12 and AIM2) are involved in the pathogenesis of several cigarette smoke-related diseases (including COPD, ALI, atherosclerosis, kidney injury, bladder dysfunction, and oral leukoplakia) and physiopathological disorders (macrophage dysfunction, endothelial barrier dysfunction, podocyte injury, and ubiquitin-mediated proteasomal processing). MyD88/NF-κB, HMGB1, production of ROS, endoplasmic reticulum stress and mitochondrial dysfunction, and Ca2+ influx are potentially involved in cigarette smoke induced-inflammasome activation. Strategies targeting ROS/NLRP3 inflammasome axis are most widely investigated and show potential therapeutic effects.